2014
DOI: 10.14260/jemds/2014/1911
|View full text |Cite
|
Sign up to set email alerts
|

Study of Clinical Profile of Non-Toxic Goiter With Special Reference to Correlation of Pathology, Lipid Profile and Antibody Level

Abstract: OBJECTIVE:To evaluate the morphology of non-toxic goiter, the role of auto-immunity and lipid abnormalities in overt and sub-clinical hypothyroid goiter patients. METHODS: A descriptive observational study was undertaken amongst goiter patients without thyrotoxic features comprising 50 randomly selected cases within the range of 12-65years. Goiter patients with thyrotoxic features, acute illness and other visceral diseases were excluded. The patients were evaluated with thyroid function tests, USG-thyroid, FNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Though thyroid neoplastic lesions are most common between 50 -60 years' age group, majority of the patients with thyroid lesions (including both neoplastic and non-neoplastic) are between 20 and 50 years. This observation is compatible with the work done by Mandrekar et al and Saha et al [7,8] The sex distribution of thyroid lesions in the present study shows a remarkable female preponderance, both in the nonneoplastic and neoplastic category. A male-to-female ratio in the present study is 1: 5.81, whereas Mandrekar et al reported this ratio to be 1: 6.1.…”
Section: Discussionsupporting
confidence: 94%
“…Though thyroid neoplastic lesions are most common between 50 -60 years' age group, majority of the patients with thyroid lesions (including both neoplastic and non-neoplastic) are between 20 and 50 years. This observation is compatible with the work done by Mandrekar et al and Saha et al [7,8] The sex distribution of thyroid lesions in the present study shows a remarkable female preponderance, both in the nonneoplastic and neoplastic category. A male-to-female ratio in the present study is 1: 5.81, whereas Mandrekar et al reported this ratio to be 1: 6.1.…”
Section: Discussionsupporting
confidence: 94%